2019
DOI: 10.1111/acv.12494
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance as a possible cause of genetic introgression from exotic into native Mauremys turtles

Abstract: The Kinmen Islands on the coastline of China represent a recent case of the protection of endangered wildlife in a demilitarized zone. These islands represent the last remaining habitat in southeastern China that supports a healthy natural population of Reeves’ turtle Mauremys reevesii. However, human‐mediated dispersal appears to have aided the establishment of an introduced population of the Chinese stripe‐necked turtle M. sinensis since the late 1990s, resulting in population mixture of the two congeners. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Ueno et al [41] revealed a cross-back hybrid between M. japonica and M. reevesii and reported that the fertility and hatchability of F1s of M. japonica and M. reevesii were not significantly different from those of the parental species, posing a potential threat to the conservation status of M. japonica , which is endemic to mainland Japan. In addition, Lee et al [9] reported that imported M. sinensis caused genetic introgression in native M. reevesii populations in the protected area, raising a critical risk to their conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueno et al [41] revealed a cross-back hybrid between M. japonica and M. reevesii and reported that the fertility and hatchability of F1s of M. japonica and M. reevesii were not significantly different from those of the parental species, posing a potential threat to the conservation status of M. japonica , which is endemic to mainland Japan. In addition, Lee et al [9] reported that imported M. sinensis caused genetic introgression in native M. reevesii populations in the protected area, raising a critical risk to their conservation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lee et al [9] reported that imported M. sinensis caused genetic introgression in native M. reevesii populations in the protected area, raising a critical risk to their conservation.…”
Section: Development Of Hrm Markersmentioning
confidence: 99%
“…As these inversions are important for the evolution of postzygotic reproductive isolation mechanisms, and thus speciation [ 120 , 121 , 122 , 123 , 124 ], this feature may contribute to the generally low species diversity in turtles [ 70 ] and their slow molecular evolution [ 125 , 126 , 127 ]. The low rate of inversions in the karyotype evolution of turtles could explain why they exhibit a high incidence of genomic introgression and why they extensively hybridize (and are often able to produce fertile offspring), even after many million years of divergence, as documented in chelid, cheloniid and geoemydid turtles [ 81 , 91 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the human-mediated movement of animals, it is becoming increasingly important to understand and manage genetic introgression and its effects [ 13 ]. Accidentally or intentionally introduced wild or domestic species can interbreed with their domesticated counterparts [ 3 , 14 , 15 , 16 ]. Gene flow from domesticated animals may carry alleles that may increase the fitness of the wild animals, so natural selection will drive introgression [ 3 ].…”
Section: Introductionmentioning
confidence: 99%